2020
DOI: 10.1123/japa.2019-0125
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Active Travel and Leisure-Time Physical Activity Relationships With Cognition Among Older Adults

Abstract: Leisure-time physical activity (LTPA) is known to benefit cognition among older adults, but the impact of active travel is unclear. To explore this relationship, data from the 2011–2014 National Health and Nutritional Examination Survey (N = 2,702; mean age = 70) were retrieved on the self-reported frequency and duration of active travel (walking/cycling for transport, >20 min), LTPA engagement (e.g., sport), and three cognitive outcomes. Four groups were created according to physical activity guidelines (6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 48 publications
0
5
0
2
Order By: Relevance
“…Inversely to recreational walking, utilitarian walking involves mandatory and fixed activities, controlled by relatively rigid schedules [23]. For that reason, utilitarian walking generally involves shorter and faster trips than recreational walking [14,21,31]. For example, the studies conducted by Kang et al [14] and by Millward et al [21] showed that utilitarian walking was, respectively, 9% to 12% faster than recreational walking.…”
Section: Categories Of Walkingmentioning
confidence: 99%
“…Inversely to recreational walking, utilitarian walking involves mandatory and fixed activities, controlled by relatively rigid schedules [23]. For that reason, utilitarian walking generally involves shorter and faster trips than recreational walking [14,21,31]. For example, the studies conducted by Kang et al [14] and by Millward et al [21] showed that utilitarian walking was, respectively, 9% to 12% faster than recreational walking.…”
Section: Categories Of Walkingmentioning
confidence: 99%
“…Although there is some evidence to suggest that recreational physical activity is more beneficial for cognitive function compared to active transport or occupational physical activity ( Phansikar et al, 2019 ), few studies have investigated this in older adults. We found a significant main effect of spending no time in recreational physical activity (relative to >30 min per day) with worse long-term memory performance.…”
Section: Discussionmentioning
confidence: 99%
“…Activities which constitute recreational physical activity (also known as leisure-time physical activity), such as dancing, gym classes or playing sports, are considered to be more beneficial for cognitive function than other physical activity modalities such as active transport (i.e., walking to the bus stop) or household chores ( Phansikar et al, 2019 ), whilst studies on the impact of occupational physical activity on cognitive function in older adults have presented mixed findings ( Rovio et al, 2007 ; Adam et al, 2013 ). The benefits associated with recreational physical activity may be partly because many recreational activities require more neuromuscular complexity, higher levels of cognitive engagement, and more social interaction (i.e., through engaging with others during group activities) ( Phansikar et al, 2019 ). However, to date, few studies have assessed differences between recreational physical activity and non-recreational physical activity against cognitive function in older adults, and this warrants further exploration.…”
Section: Introductionmentioning
confidence: 99%
“…A previous work found that self-reported PA was consistently associated with an increased risk of incident diabetes, coronary heart disease, and stroke, but not with the incidence of dementia [37]. According to different PA patterns, two studies have reported a positive association between leisure-time PA and cognition in older adults but failed to find an association with commuting mode [38,39]. About the association between sedentary time and cognitive outcomes, a recent systematic review showed that there is a lack of association between these variables in older ages [40].…”
Section: Discussionmentioning
confidence: 99%